A Fast Approach for Calculating Eigenmode of Quasi-2-D Slow Wave Structure for Sheet Electron Beam TWTs - Yin, Pengcheng; Cai, Jinchi; Xu, Jin; Yue, Lingna; Yin, Hairong; Xu, Yong; Zhao, Guoqing; Wang, Wenxiang; He, Jun; Wei, Yanyu (IEEE transactions on plasma science, 2024)
The quasi-2-D slow wave structures (quasi-2D SWSs) have mostly widely used in sheet electron beam traveling wave tubes (SEB TWTs) in recent years. This article proposed a new fast calculation method for general quasi-2D SWS, based on a higher order finite elements method (FEM). The solution processes are much faster than traditional 3-D electromagnetic simulations with the same accuracy, greatly contributing to the quick design of such SWSs. In addition, this article supplements an optimization method based on this fast calculation method and genetic algorithm. This optimization method yields the detailed structure's dimension, subject to the design goal, thus drastically boosting the design efficiency. Furthermore, these fast solutions and optimization methods can be used to investigate the new type of quasi-2D SWS. To verify this approach, this article explores a new quasi-2D SWS, with a very flat interaction impedance curve. Therefore, the methods proposed in this article will greatly contribute to the fast design, optimization, and development of quasi-2D SWSs.